"It's Scary but It's Also Exciting": Evidence of Meta-Affective Learning in Science. Issue 1 (2nd January 2019) - Radoff, Jennifer; Jaber, Lama Ziad; Hammer, David
Abstract: We study the case of Marya, a freshman engineering major who showed and spoke of a drastic shift in her feelings and approach to learning physics during an introductory course. For the first several weeks, she was anxiously manipulating equations without considering physical meaning, and she was terribly worried about being correct. By the end of the semester, however, she was sense-making and taking pleasure in it, showing and expressing an enjoyment of challenges and uncertainty. In this paper, we illustrate Marya's transformation using data from her interview and coursework, and we propose it as an example of meta-affective learning . We argue that meta-affective learning was an important part of Marya's physics learning and that it was deeply entangled with her developing epistemology.